INTEGRASI BAKAT DAN NILAI KEBAIKAN DALAM PRESPEKTIF TAFSIR TARBAWIY - Choirul Muarofah; Bunga Lailatussifa; Muhammad Ulum Nuha; Ana Rahmawati (CV. Adiba Aisha Amira, 2025)
This research aims to describe the integration of talent and goodness in the perspective of Tarbawiy interpretation. This research method uses the library research method. The library research approach is research whose object of study uses library data in the form of books as the data source. The results of this research show that there is an integration of talent and goodness in the perspective of tarbawiy interpretation. Honing talents and potential for goodness is an important process in individual self-development. In this context, talent is defined as a natural ability that a person has, while good potential refers to the capacity to contribute positively to society. This research aims to explore effective methods in identifying and developing talents and potential for goodness, including education, guidance and social experiences. The results show that a supportive environment, proper training, and intrinsic motivation play a major role in forming individuals who are not only successful in their fields, but are also committed to making a positive impact. Thus, honing talents and potential for goodness can create a more productive and caring generation, contributing to social progress and collective prosperity.